Disruption of regulatory gene GAL80 in Saccharomyces cerevisiae: effects on carbon-controlled regulation of the galactose/melibiose pathway genes. - Torchia, T E (1984)
In Saccharomyces cerevisiae, the transcriptional expression of the galactose-melibiose catabolic pathway genes is under the control of at least three regulatory genes, GAL4, GAL80, and GAL3. We have isolated the GAL80 gene and have studied the effect of a null mutation on the carbon-controlled regulation of the MEL1 and GAL cluster genes. The null mutation was achieved in vivo by replacing the chromosomal wild-type GAL80 allele with an in vitro-created GAL80 deletion-disruption mutation. Enzyme activities and RNA levels for the GAL cluster and MEL1 genes were constitutively expressed in the null mutant strain grown on glycerol-lactate and were higher than in the isogenic wild-type yeast strain when compared after growth on galactose. Carbon catabolite repression of the GAL cluster and MEL1 genes, which occurs at the level of transcription, is retained in the null mutant. Deletion of the GAL80 gene in a gal4 cell does not restore GAL cluster and MEL1 gene expression. The data demonstrate that (i) the GAL80 protein is a purely negative regulator, (ii) the GAL80 protein does not mediate carbon catabolite repression, and (iii) the GAL4 protein is not simply an antagonizer of GAL80-mediated repression.